2000
DOI: 10.1016/s0378-1097(99)00573-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and feedback-resistant γ-glutamyl kinase activity of an Escherichia coli transformant carrying a mutated proB gene of Streptococcus thermophilus

Abstract: We used a PCR‐based method to generate a single base pair mutation in the proB gene of Streptococcus thermophilus, which replaced an aspartic acid with a glycine residue at position 192 of the first proline biosynthetic enzyme γ‐glutamyl kinase. This was the first identified mutation in amino acid biosynthesis in S. thermophilus to our knowledge. The mutation caused an enhanced, feedback‐resistant γ‐glutamyl kinase activity and conferred an analogue‐resistant phenotype to an Escherichia coli transformant conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…3A). Interestingly the base changes, each of which results in an amino acid substitution within a defined (26-amino-acid) region of the GK enzyme, map closely to previously isolated mutations leading to proline overproduction in other genera (13,22,28,29,32,39) (Fig. 3B).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…3A). Interestingly the base changes, each of which results in an amino acid substitution within a defined (26-amino-acid) region of the GK enzyme, map closely to previously isolated mutations leading to proline overproduction in other genera (13,22,28,29,32,39) (Fig. 3B).…”
Section: Resultssupporting
confidence: 72%
“…1) indicated that as with the majority of systems (both prokaryotic and eukaryotic), listerial proline biosynthesis from glutamate may be regulated by proline-dependent feedback inhibition of the GK activity. Mutations leading to proline analogue resistance (and consequential proline hyperproduction) have been described for a number of organisms and have in each case been linked to mutations in GK, leading to a decreased sensitivity of the enzyme for its allosteric effector proline and its analogues (13,22,28,29,32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a site-directed mutagenesis of the V. aconitifolia P5CS, Zhang et al (22) showed that amino acid substitutions at positions 126 and 129 in the V. aconitifolia P5CS abolished proline feedback regulation. Other single amino acid mutations involving feedback regulation of GK have been recently reported in Streptococcus thermophilus and Listeria monocytogenes (26,27). In all, eight amino acid residues have been identified in six organisms as important for proline feedback regulation of GK (22-24, 26 -28, 32).…”
mentioning
confidence: 90%